Design of a Single Span Nine Metre Long Glass Bridge - D. Wittenberg (Challenging Glass Conference, 2010)
Halcrow Yolles was retained to conceptualize ideas for a glass bridge designed to span across the main lobby of a new hotel. Its defining feature, laminated glass balustrades, span continuously over the entire nine metre opening. Design work for the bridge was completed using a finite element model of the entire bridge allowing for a detailed analysis of stress concentrations in the glass at bearing bolt connections. Special attention was paid to the transportation and erection of the bridge to ensure that the large panels remained intact. This project demonstrates how state of the art glass production techniques in combination with leading edge design methodology can lead to architecturally interesting structures.